Current trends in the integration of legal thought into the international scientific space: synergy of experience and innovation - Погорецький, М.А; Топорецька, З.М (Київський національний університет імені Тараса Шевченка, ТОВ «Правова Єдність», 2024)
This review traces the foundation and growth of the Law Journal of the National Academy of Internal Affairs, published since 2011. It highlights the journal’s role as a professional forum for debates on human rights protection, crime prevention, and legislative reform amid wartime. The journal’s evolution—from a thematic collection of conference papers to a peer-reviewed, English-language publication with an international editorial board and indexing in leading bibliometric databases (ERIH PLUS, CrossRef, candidate for Scopus)—is outlined. The review examines key editorial innovations: blind peer review, rigorous academic integrity audits, strengthened requirements for article structure and citations, and open-access dissemination. It also notes a strategic shift in thematic priorities driven by the war: articles on war-crimes investigation, cybersecurity, psychological rehabilitation, and anti-corruption management. By actively engaging both domestic and foreign scholars and practitioners, the journal integrates Ukrainian legal research into the global academic community and supports the development of a rule-of-law state. The review emphasizes its importance for training highly qualified security-sector personnel and for improving legislation in the context of hybrid warfare.

Рецензія описує створення та розвиток журналу «Юридичний часопис Національної академії внутрішніх справ», який виходить друком із 2011 р. Висвітлюються його роль і місія як професійної платформи для обговорення ключових питань захисту прав і свобод людини, боротьби зі злочинністю та реформування законодавства в умовах воєнного стану. Окреслено етапи еволюції видання: від тематичного збірника наукових праць до англомовного рецензованого журналу з міжнародною редакційною радою та індексацією в провідних наукометричних базах (ERIH PLUS, CrossRef, Scopus-кандидат тощо). Розглянуто впроваджені редколегією інновації: «сліпе» рецензування, аудит академічної доброчесності, підвищені вимоги до структури та джерельної бази статей, а також відкритий доступ до контенту. Окремо відзначено зміну тематичних пріоритетів під впливом війни: публікації з розслідування воєнних злочинів, кібербезпеки, психологічної реабілітації, антикорупційного менеджменту тощо. Завдяки активному залученню вітчизняних і закордонних науковців та практиків журнал сприяє інтеграції українського юридичного дослідження у світовий науковий простір і підтримує розвиток правової держави. Рецензія підкреслює його значення для підготовки висококваліфікованих кадрів сектору безпеки та вдосконалення законодавства в умовах гібридної війни.
Сучасні тенденції інтеграції правничої думки в міжнародний науковий простір: синергія досвіду й інновацій